COVID-19 and Fieldwork: Challenges and Solutions. Issue 2 (19th April 2021) - Krause, Peter; Szekely, Ora; Bloom, Mia; Christia, Fotini; Daly, Sarah Zukerman; Lawson, Chappell; Marks, Zoe; Milliff, Aidan; Miura, Kacie; Nielsen, Richard; Reno, William; Souleimanov, Emil Aslan; et al.
ABSTRACT: This reflection article presents insights on conducting fieldwork during and after COVID-19 from a diverse collection of political scientists—from department heads to graduate students based at public and private universities in the United States and abroad. Many of them contributed to a newly published volume, Stories from the Field: A Guide to Navigating Fieldwork in Political Science (Krause and Szekely 2020). As in the book, these contributors draw on their years of experience in the field to identify the unique ethical and logistical challenges posed by COVID-19 and offer suggestions for how to adjust and continue research in the face of the pandemic's disruptions. Key themes include how contingency planning must now be a central part of our research designs; how cyberspace has increasingly become "the field" for the time being; and how scholars can build lasting, mutually beneficial partnerships with "field citizens, " now and in the future.